(untitled) (PROKLA. Journal of Critical Social Science, 1997)
This paper analyzes the transition of the agricultural sector in East Germany from 1990 to 1997. One preliminary finding is that the East-German agrarian structure differs in several respects from the one in the westem part of the country. The author argues that it was due to the strategic behavior of the political actors during the transition that conflicts of interest caused by structural divergency were avoided. Most important in this respect was the policy choice of the West German farmers’ interest organization. In order to maintain its representational monopoly, it managed to integrale East German farmers by modifying the ideological basis of membership integration and the instruments of rhetoric used in the past. By integrating East German farmers into the sectoral policy network, intranational conflicts over state transfers were avoided and East Gennan agriculture found itself in a good position to improve its competitiveness and its influence on the reform ofnational and European agricultural policies.